2019
DOI: 10.21565/ozelegitimdergisi.440429
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Levels and Expectations of Students with Disabilities in Physical Education and Sports Departments of Universities

Abstract: Bu araştırma, beden eğitimi ve spor bölümlerinde okuyan engelli öğrencilerin bölümlerine uyumlarını vebeklentilerini tespit etmeye yöneliktir. Nicel ve nitel yaklaşımların bir arada kullanıldığı, karma yaklaşım desenlerinden açımlayıcı sıralı desen ile kurgulanan araştırma, 2015-2016 Eğitim-Öğretim yılında Türkiye genelindeki 21 üniversitenin beden eğitimi ve spor bölümlerinde öğrenim gören tüm engelli öğrencilerin katılımıyla gerçekleşmiştir. Araştırmanın nicel bölümüne, 27'si görme, 9'u işitme, 38 'i bedense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…It has been reported that parents with intellectual disability generally welcome their children's participation in sports activities (18,19,20) and that parents' awareness of the effects of sports is at a moderate level (21). Although parents with intellectual disability welcome students' participation in sports, it is known that these students struggle with various problems in sports participation due to policies, environment and personal problems (4,22,23,24,25). Therefore, it is limited in an important issue such as the evaluation of parents' views on the restrictions faced by students with intellectual disabilities in their participation in physical activities and sports education.However, the number of studies on the reasons for the difficulties encountered by students with intellectual disabilities in their participation in sports is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that parents with intellectual disability generally welcome their children's participation in sports activities (18,19,20) and that parents' awareness of the effects of sports is at a moderate level (21). Although parents with intellectual disability welcome students' participation in sports, it is known that these students struggle with various problems in sports participation due to policies, environment and personal problems (4,22,23,24,25). Therefore, it is limited in an important issue such as the evaluation of parents' views on the restrictions faced by students with intellectual disabilities in their participation in physical activities and sports education.However, the number of studies on the reasons for the difficulties encountered by students with intellectual disabilities in their participation in sports is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Gençlik ve Spor İl Müdürlükleri bünyesinde faaliyet gösteren gençlik merkezleri; ülke gençliğinin sosyo-kültürel gelişimleri için çeşitli faaliyet alanlarına sahiptir. Gençlik merkezlerinde açılan kurslar ve düzenlenen organizasyonlar tüm fertler için farklı ortamlar oluşturarak ülke gençliğinin hem yeteneklerinin gelişimini hem de akran ilişkileriyle sosyalleşmelerini sağlamaktadır (Aycan, 2005;Sönmezoğlu ve ark., 2014;Karabulut ve Pulur, 2011;Namlı ve Suveren, 2019). Sportif anlamda taşra teşkilatı bünyesinde çeşitli branşlarda sporcu yetiştirilmesi ile de görevlendirilen İl Müdürlükleri, antrenörleri vasıtasıyla çeşitli yaş grupları için branşlara yönelik eğitim vermektedirler.…”
Section: Introductionunclassified